Functions and regulation of T cell-derived interleukin-10. (August 2019) - Neumann, Christian; Scheffold, Alexander; Rutz, Sascha
Abstract: Interleukin (IL)-10 is an essential anti-inflammatory cytokine and functions as a negative regulator of immune responses to microbial antigens. IL-10 is particularly important in maintaining the intestinal microbe-immune homeostasis. Loss of IL-10 promotes the development of inflammatory bowel disease (IBD) as a consequence of an excessive immune response to the gut microbiota. IL-10 also functions more generally to prevent excessive inflammation during the course of infection. Although IL-10 can be produced by virtually all cells of the innate and adaptive immune system, T cells constitute a non-redundant source for IL-10 in many cases. The various roles of T cell-derived IL-10 will be discussed in this review. Given that IL-10 is at the center of maintaining the delicate balance between effective immunity and tissue protection, it is not surprising that IL-10 expression is highly dynamic and tightly regulated. We summarize the environmental signals and molecular pathways that regulate IL-10 expression. While numerous studies have provided us with a deep understanding of IL-10 biology, the majority of findings have been made in murine models, prompting us to highlight gaps in our knowledge about T cell-derived IL-10 in the human system.